Identities, conflicting behavioural norms and the importance of job attributes - Giovanni Russo; Edwin van Hooft (Institute for the Study of Labor (IZA), 2009)
The paper empirically expounds the richness of the identity approach to labor market behavior by allowing individuals to experience identity conflict. Specifically, it investigates the relationship between the importance individuals attach to labor-market activities - which is influenced by the identity to which they adhere - and their preferences for job attributes. The analysis shows that individuals who consider labor-market success as instrumental for achieving their life goals tend to attach importance to job characteristics such as pay level and career and training opportunities. Individuals for whom non-labor market activities are important and in conflict with labor market activities are found to attach importance to the possibility of working on a convenient time schedule. Moreover, consistently with the identity approach to labor-market behavior, men appear to resolve the conflict between career and non-work activities in favor of the former. Finally, unobserved factors that increase the desire to work part-time have a negative impact on the likelihood of attaching importance to training and career opportunities offered by the job.
Keywords: J22; J24; Z13; 330; Job attributes; social identity; role conflict; part-time; Arbeitsethik; Persönlichkeitspsychologie; Soziale Rolle; Arbeitsgestaltung; Erwerbsverlauf; Arbeitszeit; Zeitallokation; Geschlecht; Niederlande